Pengembangan Bahan Ajar Mata Pelajaran Pendidikan Agama Islam oleh Guru Tingkat Sekolah Dasar - Afifah ‘ ‘Ulya; Zulhiza Romi; Elfa Maijuana; Sasmi Nelwati; Misra Misra (Mathematics Education Study Program, 2025)
Teaching materials are all forms of materials used in carrying out teaching and learning activities. Teaching materials can include materials about knowledge, skills, and attitudes that must be achieved by students related to certain learning outcomes. The purpose of this study is to discuss the objective conditions of PAI teaching materials, the problems faced by PAI teachers in developing teaching materials, and the steps taken by PAI teachers to develop teaching materials at SD Negeri 04 Tarandam. This study used a qualitative approach, then the instruments used were observation, interviews, and documentation. The result of the research is that the teacher is responsible for compiling the Module while the principal PAI material that has been determined is developed by the teacher himself. The problems faced by teachers are determining teaching materials that are relevant to the Learning Outcomes and Flow of Learning Objectives, lack of infrastructure, and problems that arise from students who do not understand the material coupled with limited teaching material sources. Therefore, the importance of developing teaching materials is for learning activities in the classroom, because the development of teaching materials can make it easier for students to understand the material and be more active in the PAI learning process.